1988
DOI: 10.1139/v88-488
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopalladation of trimesitylarsine. The X-ray crystal structure for

Abstract: (1), Pd-P 2.318(1), Pd-C 2.056(3), and Pd-As 2.437(1) A; As-Pd-C196.5(1), CI-Pd-P 90.9(1), P-Pd-C 93.7(1), As-Pd-C 78.9(1), As-Pd-P 172.6(1), and CI-Pd-C 171.7(1)". The average C-P-C angle (104.3(1)") is smaller than expected and is rationalized on the basis of steric effects operative within the complex. Pd-P 2,318(1), Pd-C 2,056(3) et Pd-As 2,437(1) A; As-Pd-C1 96,5(1), CI-Pd-P 90,9(1), P-Pd-C 93,7(1), As-Pd-C 78,9(1), As-Pd-P 172,6(1) et C1-Pd-C 171,7(1)". L'angle C-P-C moyen (104,3(1)") est plus faible que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The X-ray crystallographic analysis revealed that 8 has a Cl-bridged dinuclear structure where a half of the dinuclear structure is an asymmetric unit. In spite of the bulkiness of the ligands, bond lengths and angles around the central palladium atom in 8 are similar to those of previous Cl-bridged dinuclear complexes bearing a common triarylphosphine [41][42][43][44]. There is only one reported example of a neutral organopalladium(II) chloride complex, Pd(6)(allyl)Cl, bearing a biaryl-based phosphine ligand [20].…”
Section: Resultssupporting
confidence: 77%
“…The X-ray crystallographic analysis revealed that 8 has a Cl-bridged dinuclear structure where a half of the dinuclear structure is an asymmetric unit. In spite of the bulkiness of the ligands, bond lengths and angles around the central palladium atom in 8 are similar to those of previous Cl-bridged dinuclear complexes bearing a common triarylphosphine [41][42][43][44]. There is only one reported example of a neutral organopalladium(II) chloride complex, Pd(6)(allyl)Cl, bearing a biaryl-based phosphine ligand [20].…”
Section: Resultssupporting
confidence: 77%
“…Both palladium centres show square planar geometries. The Pd Á/C bond lengths of 2.028 Å are within observed ranges for similar complexes [13,17]. The Pd Ã/P bond lengths are shorter (2.214 Å ) than expected for a non-cyclometallated Pd phosphine complex (2.24 Á/2.35 Å ) [18] 3.…”
Section: Chemistry Of Phospha-palladacyclessupporting
confidence: 70%
“…Salt metathesis with tetrabutylammonium halides yields in halogen-bridged dimeric complexes, equally stable, but less soluble in non-coordinating solvents [13]. Addition of coordinating solvents or donor ligands increases the solubility due to the formation of monomeric complexes.…”
Section: Chemistry Of Phospha-palladacyclesmentioning
confidence: 99%
“…2). The molecular [54,55] even in the structure with two mesityl substituents at the donor P atom [56].…”
Section: Dinuclear Coordination Complex [(M-cl)pdcl(hl 1 )] 2 mentioning
confidence: 99%
“…These values are typical for other chloro-bridged phosphapalladacycles [24,51e53]. The length difference for the PdeCl bonds in 1, 0.0126 A, is greater than that observed in IeIII, 0.001e0.005 A; however, the difference is smaller than that in IV, 0.020 A and significantly smaller than in palladacycles with the (sp 3 )C donor atom, in which the PdeCl bond trans to the P atom is significantly shorter, up to 0.088 A [56]. These observations suggest similar trans influence of the (sp 2 )C atom and the heteroatom in the PPh 2 fragment in complexes 1 and IeIV and a greater trans influence of the (sp 3 )C donor atom compared to its sp 2 -hybridized counterpart [22].…”
Section: Dinuclear Coordination Complex [(M-cl)pdcl(hl 1 )] 2 mentioning
confidence: 99%